Cost-effectiveness of nurse-delivered cognitive behavioural therapy (CBT) compared to supportive listening (SL) for adjustment to multiple sclerosis - I. Mosweu; R. Moss-Morris; L. Dennison; T. Chalder; Paul McCrone (Health Economics Review, 2017)
Background: Cognitive Behavioural Therapy (CBT) reduces distress in multiple sclerosis, and helps manage adjustment, but cost-effectiveness evidence is lacking. Methods: An economic evaluation was conducted within a multi-centre trial. 94 patients were randomised to either eight sessions of nurse-led CBT or supportive listening (SL). Costs were calculated from the health, social and indirect care perspectives, and combined with additional quality-adjusted life years (QALY) or improvement on the GHQ-12 score, to explore cost-effectiveness at 12 months. Results: CBT had higher mean health costs (1610, 95% CI, -187 to 3771) and slightly better QALYs (0.0053, 95% CI, -0.059 to 0.103) compared to SL but these differences were not statistically significant. This yielded 301,509 per QALY improvement, indicating that CBT is not cost-effective according to established UK NHS thresholds. The extra cost per patient improvement on the GHQ-12 scale was 821 from the same perspective. Using a 20,000, threshold, CBT in this format has a 9% probability of being cost effective. Although subgroup analysis of patients with clinical levels of distress at baseline showed an improvement in the position of CBT compared to SL, CBT was still not cost-effective. Conclusion: Nurse delivered CBT is more effective in reducing distress among MS patients compared to SL, but is highly unlikely to be cost-effective using a preference-based measure of health (EQ-5D). Results from a diseasespecific measure (GHQ-12) produced comparatively lower Incremental Cost-Effectiveness Ratios, but there is currently no acceptable willingness-to-pay threshold for this measure to guide decision-making.
Keywords: 330; Multiple sclerosis; Cost-effectiveness; Costs; Cognitive behavioural therapy; Distress; Anxiety